F. Brentano and K. Twardowski: Some Traces of Their Influence on the Contemporary Ukrainian Scholars - Karivets, Ihor (Problemos, 2019)
n this article, the author considers the particularities of Franz Brentano’s psychognosy (descriptive psychology) in the context of notion of “basic” or “analytic” truths and his methodological approaches to scientific, philosophical investigations as well as his influence upon Kasimir Twardowski, who was the pupil of Brentano and accepted the main points of his methodological program.The author also stresses that the study of Brentano’s and Twardowski’s heritage is important for tracing the origin of scientific/analytic philosophy. It is very important to investigate Brentano-Twardowski relations in the context of the concept of “basic truths” or “analytic truths”. Brentano stresses that “basic truths” can be found thanks to “psychognosy” or “pure psychology”. For Twardowski, psychology is the base for philosophical investigations because it helps to understand the formation of notions and judgements.This article is also dedicated to the inquiries of Brentano’s and Twardowski’s legacy provided by Ukrainian scholars Borys Dombrowskiy and Yanosh Sanotskiy. The reception of Brentano’s theory of judgement in Dombrowskiy’s works and the problem of Brentano’s psychologism in Sanotskiy’s works were examined.
Keywords: Borys Dombrowskiy; Franz Brentano; Kasimir Twardowski; Yanosh Sanotskiy; Lvіv Philosophical School